Two Mysterious Tiny Katydids from the Ecuadorian Andes (Orthoptera: Tettigoniidae: Hexacentrinae) - Braun, Holger (2016)
Two very small katydids living in upper montane rainforest and elfin forest at 2500–3200 m on the eastern Andean cordillera of south Ecuador are described: Nubimystrix consuelo gen. et sp. nov. and N. amarui sp. nov. They have strongly reduced wings and feature a confusing mixture of morphological characteristics, such as spiny fore tibiae, unconcealed tympana, and tiny auditory spiracles. Apparently these katydids represent a third South American genus of the small subfamily Hexacentrinae. Males of both species produce at night ultrasound calling songs with carrier frequency ranges from about 23 to 31 kHz. While the song of the first species consists of brief calls, males of the other call very continuously, so that especially the presence of the latter can easily be assessed using an ultrasound detector. With an acoustic record at 3210 m, N. amarui is also the highest-occurring katydid species in the investigated area. Some interrelated aspects of biogeography, ecology, and bioacoustics are discussed.